Building Character And Literacy Skills Of Primary School Students Through Puppet Contemplative Sukuraga - Nurasiah, Iis; Azwar Uswatun, Din; Rizqia Amalia, Arsyi (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2017)
Education is a process of enculturation, serves bequeath the values and achievements of the past to the future generations. Values and achievement that is the pride of the nation and the people make it known to other nations. In addition to bequeath, education also has a function to develop the cultural values and achievements of the past into the nation's cultural values corresponding to the life of the present and future, as well as developing new achievements into new character of the nation. Therefore, education, culture and national character is at the core of an educational process. literacy skills expected to provide supplies for children in reading, writing, and appreciating and responding to all types of communication. Creating literat generation requires a long process and means conducive. It begins with small and family environment, and are supported or developed in school, social environment, and the work environment. Puppet Sukuraga laden with enlightenment, education, reflection, invite people really keep up with both his body as a God-given mandate in accordance with the nature of their respective functions.